Fate of nanoplastics in the environment: Implication of the cigarette butts. (1st January 2021) - El Hadri, Hind; Lisa, Jesus Maza; Gigault, Julien; Reynaud, Stéphanie; Grassl, Bruno
Abstract: Fate, transport and accumulation of nanoplastics have attracted considerable attention in the past few years. While actual researches have been focused on nanoplastics dispersed or aggregated in different environmental system, no study have been focused on the possibility that nanoplastics are co-transported with other natural or anthropogenic materials. Therefore, the large quantity of debris released in the environment, such as cigarette butts (CGB), could be part of the nanoplastics fate and behavior. Here we show the considerable sorption capacities of cigarette filters for nanoplastics. To address this topic, we chose polystyrene-based nanoplastics with similar state of charge (according to the physico-chemical characteristic of the zeta potential −45 to −40 mV) but with different sizes (50–800 nm) and morphologies. A kinetic approach to sorption in fresh water (pH = 8.05; 179.5 μS cm −1 ) at room temperature was carried out by means of the flow field flow analysis method (AF4) to determine the partition coefficients and water sampling rates between nanoplastics and cigarette butts. Using different models of, more or less environmentally relevant, nanoplastics (NPTs) and adequate analytical strategies, we found partition coefficients between the NPTs and CGBs ranged from 10 2 to 10 4 in freshwater conditions. We demonstrated that the physical features of the NPTs (size and morphology) have an influence on the sorption behaviour. Asymmetrical shaped NPTs with broader size distribution seems to be mostly retained in the CGBs after longer equilibration time. This result shows the importance of the NPTs features on the mechanisms governing their transfer and fate in the environment through environmental matrices, especially when other materials are involved. We anticipate our work to be a starting point for investigating the co-transport of NPTs with other materials present in the environment (natural and anthropogenic). Graphical abstract: Image 1 Highlights: The nanoplastic sorption by cigarette filters was evaluated in pure and freshwater. The sorption was addressed for nanoplastics of various morphologies and dispersity. A kinetic approach gives cigarette filters partition coefficient within 10 2 -10 4 .